2020
DOI: 10.2337/dc20-1447
|View full text |Cite
|
Sign up to set email alerts
|

Six Months of Hybrid Closed-Loop Versus Manual Insulin Delivery With Fingerprick Blood Glucose Monitoring in Adults With Type 1 Diabetes: A Randomized, Controlled Trial

Abstract: OBJECTIVE To investigate glycemic and psychosocial outcomes with hybrid closed-loop (HCL) versus user-determined insulin dosing with multiple daily injections (MDI) or insulin pump (i.e., standard therapy for most adults with type 1 diabetes). RESEARCH DESIGN AND METHODS Adults with type 1 diabetes using MDI or insulin pump without continuous glucose monitoring (CGM) were randomized to 26 weeks of HCL (Medtronic 670G) or cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 38 publications
(51 reference statements)
3
75
1
3
Order By: Relevance
“…The first commercialized standard hybrid closed-loop (s-HCL) system (Medtronic MiniMed ™ 670G) infuses micro boluses of insulin to reach a glucose target of 120 mg/dL. The pivotal trial showed a 5.5% increase in time in range (TIR, between 70 and 180 mg/dL) (7,8), and real-life data showed improved outcomes and the superiority of 670G compared to any other treatment modality (multi-daily injections [MDI], CSII or sensor-augmented pump [SAP]) (9)(10)(11)(12)(13). One real-life study on 92 individuals between 2-25 years of age found a decrease in HbA1c of -0.3% after six months of 670G use (14), while another study on 111 children and adolescents aged 3 to 16 years found an improvement in sensor-specific measures of glycemic control (but not HbA1c) that lasted throughout the first year of treatment (15).…”
Section: Introductionmentioning
confidence: 99%
“…The first commercialized standard hybrid closed-loop (s-HCL) system (Medtronic MiniMed ™ 670G) infuses micro boluses of insulin to reach a glucose target of 120 mg/dL. The pivotal trial showed a 5.5% increase in time in range (TIR, between 70 and 180 mg/dL) (7,8), and real-life data showed improved outcomes and the superiority of 670G compared to any other treatment modality (multi-daily injections [MDI], CSII or sensor-augmented pump [SAP]) (9)(10)(11)(12)(13). One real-life study on 92 individuals between 2-25 years of age found a decrease in HbA1c of -0.3% after six months of 670G use (14), while another study on 111 children and adolescents aged 3 to 16 years found an improvement in sensor-specific measures of glycemic control (but not HbA1c) that lasted throughout the first year of treatment (15).…”
Section: Introductionmentioning
confidence: 99%
“…
The JDRF Australia Adult Hybrid Closed Loop (HCL) Study Group recently published results of the first randomized trial (ACTRN12617000520336, HREC-D088/16) of the commercially available HCL MiniMed™ 670G system (Medtronic, Northridge, CA). 1,2 The trial compared six-months HCL vs. standard therapy [self-monitoring of blood glucose (SMBG) with multiple-daily-injections or continuous subcutaneous insulin infusion (CSII) without continuous glucose monitoring (CGM)] in adults with type 1 diabetes. It demonstrated that HCL improves glucose management, including time-inrange (70-180 mg/dl), all other CGM metrics, HbA1c and 1,5 anhydroglucitol.
…”
mentioning
confidence: 99%
“…It demonstrated that HCL improves glucose management, including time-inrange (70-180 mg/dl), all other CGM metrics, HbA1c and 1,5 anhydroglucitol. 1 As there is limited evidence regarding HCL use with exercise 3 we conducted a sub-study comparing glucose management in 10 adults with type 1 diabetes undertaking 45 min of moderate-intensity exercise (MIE) and high-intensity interval exercise (HIIE) in random order separated by 7-days, with 6 subjects (computer) randomized to HCL and 4 to standard therapy. After 5 min warm-up (25% VO2max) MIE comprised 40 min of continuous exercise at 70% of their anerobic threshold.…”
mentioning
confidence: 99%
“…31,35 Randomized controlled trials and meta-analyses have shown that artificial pancreas systems increase the time spent in target glucose range, reduce time spent in hyperand hypoglycemia, reduce glycated hemoglobin (HbA1c), decrease mean glucose levels and glucose variability, and improve diabetes-specific positive well-being and quality of life compared with conventional insulin pump therapy and sensor-augmented pumps equipped only with low-glucose suspend feature enabling automated suspension of insulin delivery at a threshold glucose level. 5,13,[36][37][38][39][40][41][42][43][44][45] Nonetheless, clinically significant hypoglycemic and hyperglycemic episodes still occur with the artificial pancreas. 13,36,46 Therefore, one of the main goals of research focused on technology for the management of T1D is to develop an artificial pancreas potentially capable of leading to near-normal glucose levels accompanied by a percentage of time spent in target glucose range as high as possible, with low glucose variability and without the occurrence of clinically significant hypoglycemic or hyperglycemic episodes.…”
Section: Dual-hormone Artificial Pancreas For T1dmentioning
confidence: 99%